Synthesis of Human Antibodies Against HBsAg in Newly Established Chinese Hamster Lung (CHL-YN) Cell Line - Meutia Diva Hakim; Noriko Yamano- Adachi; Takeshi Omasa; Marselina Irasonia Tan; Lia Dewi Juliawaty; Ernawati Arifin Giri-Rachman (Journal of Mathematical and Fundamental Sciences, 2023)
Hepatitis B immunoglobulin (HBIG) is an effective treatment for hepatitis B, including postexposure prophylaxis of HBV infection, prevention of HBV reinfection in liver transplant patients, and reducing sexual transmission. This study investigated the synthesis of human IgG antibodies that specifically target HBsAg subtype adr in CHL-YN cells, a newly established cell line that grows faster than CHO-K1. To achieve the synthesis of human IgG antibodies, a plasmid vector encoding DNA sequences for human IgG antibodies against HBsAg was constructed and then transiently transfected into CHL-YN cells. The expression and antigen-binding capacity of the recombinant human IgG antibodies were analyzed using western blot and ELISA. The results showed successful expression and secretion of human IgG antibodies that recognize HBsAg subtype adr in CHL-YN cells. The ELISA test confirmed the specificity of the human IgG antibodies towards HBsAg subtype adr. Thus, this study concluded that human IgG antibodies that target HBsAg subtype adr were transiently expressed in CHL-YN cells.